1982
DOI: 10.1161/01.cir.66.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on ventricular function in patients with recent myocardial infarction.

Abstract: SUMMARY We evaluated the effects of 6 months of exercise training (bicycle ergometry, walking and jogging) on exercise performance and ventricular function in patients with recent myocardial infarction. Fifteen patients were selected on the basis of myocardial infarction at least 6 weeks but not more than 6 months before the study and age younger than 65 years. The patients were evaluated by maximal treadmill exercise testing and radionuclide angiography at rest and exercise before and after training.Before ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…26 Cobb et al reported that left ventricular function at rest and during exercise revealed no significant change after exercise training, though improvement in exercise performance was observed. 27 We found that the plasma BNP level of the training group with anterior MI did not tend to decrease over the study period while that of the nontraining group with anterior MI decreased significantly.…”
Section: Nontraining Inferior Groupmentioning
confidence: 60%
“…26 Cobb et al reported that left ventricular function at rest and during exercise revealed no significant change after exercise training, though improvement in exercise performance was observed. 27 We found that the plasma BNP level of the training group with anterior MI did not tend to decrease over the study period while that of the nontraining group with anterior MI decreased significantly.…”
Section: Nontraining Inferior Groupmentioning
confidence: 60%
“…Peripheral adaptations similar to those seen in healthy subjects are thought to occur in this patient group (Clausen 1976;Detty et ale 1971), although there is some debate concerning the presence of central changes (Cobb et al 1982;Ehsani 1987;Franklin et ale 1992;Hagberg 1991;Hung et al 1984). The latter may be partially attributable to the different methods used to determine changes in stroke volume.…”
Section: The Physiological Effects Of Exercise In Patients After a Mymentioning
confidence: 72%
“…The perfusion in the distribution of dilated artery has been shown to improve progressively until 3 months [4]. Many authors have not found any difference in LV ejection fraction values in the third and sixth month following AMI [5][6][7]. This makes us hypothesize that majority of the improvement occurs in the first 3-4 months.…”
Section: Introductionmentioning
confidence: 95%